Chylous Ascites in a Newborn with Gastroschisis. Case Report - Zalles-Vidal, Cristian Ruben; Peñarrieta-Daher, Alejandro; Ibarra-Rios, Daniel; Fernandez-Portilla, Emilio; Bracho-Blachet, Eduardo (Journal of Neonatal Surgery, 2016)
Chylous ascites is a rare disease, only two cases associated with gastroschisis have been published. We report a case treated conservatively with total parenteral nutrition (TPN) and octreotide. We reviewed the literature about management options for the chylous ascites.